Suction-Monitored Direct Shear Test on Unsaturated Sand and Sand-Kaolin Clay Mixture - Purwana, Yusep Muslih; Nikraz, Hamid (Jurnal Geoteknik, 2014)
One of the common devices for unsaturated soil strength testing is suction-controlled direct shear. In this device, suction is adjusted by controlling water pressure and air pressure during the test. Suction was generated indirectly by adjusting the specimenâs water content to the desired value. During the test, suction was monitored using the attached tensiometer. Thus in this method, pore water and pore air pressure control is no longer required. The tests were carried out using sand and sand-kaolin clay mixtures in 95:5 and 90:10 proportions. The results indicates that shear strength with respect to matric suction exhibits a bilinear envelope with an initial value of fb is higher than the effective internal friction fÂ¢. Despite the suction capacity of the tensiometer was relatively low, this device was effective for low air entry soils such as sand or sand with relatively small portion of fine grained material. Keywords: Sand-kaolin clay mixtures, suction-monitored direct shear test, unsaturated shear strength